RESEARCH SKILLS AS AN INDICATOR OF READYNESS OF HIGH SCHOOL STUDENTS TO CREATIVE WORK (Pedagogy of Higher and Secondary Education, 2004)
The article deals with the specificity o f investigating skills as an exponent o f future teachers’ readiness to the creative professional activities, their classification is given.